The reflection of cultural characteristics in the education of Vietnam = Refleksje na temat charakterystyki kulturowej w edukacji w Wietnamie - Tran Van Thuc; Truong Thuy Dung (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Culture and education have gone together over 2000 years, making the foundations for development of Vietnam. The authors discuss connections between culture and education. They claim that not only the education system contains the characteristics of culture in general, but also reflects the unique imprints of culture. In this case they concentrate on Vietnamese culture and the general view of it was presented in the first part of the text. In the next part the characteristic of education in Vietnam is briefly described. Then they specify how the cultural characteristics reflect on Vietnamese education. The main elements of the connection is inheritance and continuity of culture.
Keywords: kultura; edukacja; dziedzictwo; Wietnam; culture; education; inheritance; Vietnam